THE INFLUENCING FACTORS OF INTERNATIONAL ENTREPRENEURIAL INTENTION AMONG GENERATION Z IN INDONESIA - Kesumahati, Erilia; Winshen; Wisnu Yuwono (Program Sarjana Manajemen Universitas Internasional Batam, 2025)
The newer generation, particularly Generation Z (Gen Z), has a distinct perspective due to the advancements in digital technology. Currently, a significant number of them are interested in establishing their own enterprises, and a few of them are internationally recognized. The objective of this investigation is to investigate the factors that influence the international entrepreneurial intention of Gen Z in creating international ventures, such as entrepreneurship education, entrepreneurial opportunity identification, entrepreneurial motivation, and family support. The survey employed purposive sampling and a quantitative methodology, included 265 Gen Z respondents from Indonesia. The SmartPLS 3.0 results indicated that entrepreneurship education, entrepreneurial motivation, and family support each had a significant impact on international entrepreneurial intention. Furthermore, entrepreneurial motivation had significant impact on family support. However, entrepreneurial opportunity identification did not have a significant effect on international entrepreneurial intention. These results suggest that the emotional and pedagogical support provided to the younger generation significantly influences their inclinations to pursue international entrepreneurship.